2010
DOI: 10.1007/s10163-009-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and estrogenic activity of colored livestock wastewater after electrolysis treatment

Abstract: Livestock wastewater is treated by activated sludge treatment. Untreated livestock wastewater has high estrogen activity because animal excreta contains estrogen. When activated sludge treatment is applied, the estrogen activity declines or is lost. However, the color of treated livestock wastewater is deep brownish-red because of the decomposition of organic compounds or the synthesis of metabolites. Discharging colored wastewater to the environment could cause some problems, so it is necessary to decolorize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…That was the reason of effective color removal and poor COD change in anodic chamber. Similar results were obtained after colored livestock wastewater electrolysis (without membrane) treatment [33]. It can be concluded that it is possible to decolorize effluent after biological treatment by electrolysis, but the maximum removal of COD was approximately 30% when achieving almost complete decolorizing.…”
Section: Color and Cod Removal With Microfiltration Membrane (Mfm) Elsupporting
confidence: 79%
“…That was the reason of effective color removal and poor COD change in anodic chamber. Similar results were obtained after colored livestock wastewater electrolysis (without membrane) treatment [33]. It can be concluded that it is possible to decolorize effluent after biological treatment by electrolysis, but the maximum removal of COD was approximately 30% when achieving almost complete decolorizing.…”
Section: Color and Cod Removal With Microfiltration Membrane (Mfm) Elsupporting
confidence: 79%
“…In recent years, many researchers have devoted themselves to the development of advanced oxidation methods to treat wastewater, mainly including chemical oxidation, Fenton oxidation, wet air oxidation, supercritical water oxidation, photochemical oxidation and electrochemical oxidation [5][6][7][8][9]. Among many advanced oxidation methods, electrocatalytic oxidation technology, as the green chemical technology, can degrade complex organic pollutants in wastewater into non-toxic small molecular organic compounds or carbon dioxide and water through mineralization of various organic pollutants [10][11][12][13][14][15]. A large number of studies have shown that electrocatalytic oxidation technology is one of the effective methods for the treatment of high concentration pharmaceutical wastewater, but the technology is still in the initial stage [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using conventional sewage treatment technology is difficult to achieve national and local control standards. Advanced oxidation deep treatment technology is an important method to meet the sewage discharge standard, and electrochemical catalytic oxidation [2] [3] [4] is fast and efficient in COD removal, strong in the control process, and easy to use with other unit process. It can deal with both inorganic and organic pollutants without the addition of REDOX agents and secondary pollution, and it is an environmentally friendly green water treatment technology.…”
Section: Introductionmentioning
confidence: 99%